About Health Sciences and Disease - Nko'o Amvene, Samuel (HEALTH SCIENCES AND DISEASE, 2024)
Health Sciences and Disease, is an open source, peer reviewed medical journal that covers all aspects of medicine, pharmacy, biomedical and health sciences, including public health and societal issues. It is an “online first” publication, which means that all the publications articles appear on the website before being included in the print journal. The papers are published in full on the website, with open access. Our vision is to be the leader medical journal in our region. Our mission is to inform and educate all the health professionals and to promote constructive debate on health issues that matter in the management not only of diseases but of health as a whole. Health Sciences and Disease is the official publication of the Faculty of Medicine and Biomedical Sciences of the University of Yaoundé I. Its team is based in Yaounde (Cameroon). Acceptance of manuscripts is based on the originality, the quality of the work and validity of the evidence, the clarity of presentation, and the relevance to our readership. Publications are expected to be concise, well organized and clearly written. Authors submit a manuscript with the understanding that the manuscript (or its essential substance) has not been published other than as an abstract in any language or format and is not currently submitted elsewhere for print or electronic publication.